Managing electronic records - Saffady, William, 1944-; Association of Records Managers and Administrators (Lenexa, Kan. : ARMA International, 2009)
The fourth edition of this best-selling classic provides a comprehensive discussion of records management concepts and methods as they apply to electronic records. It is intended for anyone with responsibilities for creating, maintaining, managing, controlling, and using electronic records created by computer, audio, and video systems. The treatment is practical rather than theoretical. --from publisher description
Concepts and issues -- Storage media for electronic recordkeeping -- File formates for electronic records -- Inventorying electronic records -- Retention schedules for electronic records -- Managing vital electronic records -- Managing electronic files and media.
Includes index.
"Suggestions for further study" : p. 225-226.
Keywords: Computer files -- Management; Information storage and retrieval systems -- Management; Electronic records -- Management; Records -- Management; x; Gestion des documents -- Informatique; x